2020
DOI: 10.1088/1361-648x/ab9c5d
|View full text |Cite
|
Sign up to set email alerts
|

Composition dependence of the superconducting properties of UTe2

Abstract: A better understanding of the synthesis conditions, composition and physical properties of UTe2 are required to interpret previously reported unconventional superconductivity. Here we report how the superconducting properties of single crystals depend on the ratio of elements present in their synthesis by chemical vapour transport. We have obtained crystals with the highest reported ambient pressure T c and a larger superconducting heat capacity jump from a growth with a U:Te ratio different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…Finally, recent work has shown that there are two well-separated transitions under pressure (29,30), which supports the idea that there are two nearly degenerate symmetry breaking possibilities for a superconducting state in UTe2. Both studies show that the splitting diminishes rapidly with decreasing pressure, with one study confirming the existence of splitting at ambient pressure (30), suggesting that the small splitting evident in our heat capacity experiments may be sensitive to sample quality and difficult to discern in other published work (2,31).…”
mentioning
confidence: 53%
“…Finally, recent work has shown that there are two well-separated transitions under pressure (29,30), which supports the idea that there are two nearly degenerate symmetry breaking possibilities for a superconducting state in UTe2. Both studies show that the splitting diminishes rapidly with decreasing pressure, with one study confirming the existence of splitting at ambient pressure (30), suggesting that the small splitting evident in our heat capacity experiments may be sensitive to sample quality and difficult to discern in other published work (2,31).…”
mentioning
confidence: 53%
“…An alternative picture without phase transition between SC1 and SC2 cannot be excluded, since the upturn of H c2 could result from a tight balance between the orbital limitation and the increase of the coupling λ with field 37 . We further note that, at ambient pressure and zero magnetic field, a single superconducting transition was identified in 23,24,40 but two separated superconducting transitions were reported in 28,41 . Figure 1(b) presents a combination of low-temperature magnetic-field versus field-angle phase diagrams of UTe 2 obtained by Ran et al 33 and Knebel et al 37 It summarizes the effect of magnetic fields applied in the (a, b) and (b, c) planes.…”
mentioning
confidence: 62%
“…The sample dependence on superconductivity and chemical composition is extensively studied in ref. [23] and a significant difference in composition ratio Te/U is reported between superconducting and non-superconducting samples, where the nonsuperconducting sample shows systematically larger Te/U ratio.…”
Section: Crystallographic Characterizationmentioning
confidence: 91%
“…[21,22] As inferred from the absence of superconductivity in single crystals used for earlier studies, relatively small lattice imperfection has strong impact on physical properties. Even in superconducting samples, superconducting transition temperature varies from about 1.5 K up to 2 K [18,23,24]. Previous study proposed that the emergence of superconductivity would be caused by slight Te-deficiency [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation